Analysis of Competitive Strategies in Culinary Businesses to Increase Sales Revenue in Binamu District, Jeneponto Regency - Sugianto; Tahir, Thamrin; Bado, Basri; Hasan, Muhammad; Dinar, Muhammad (Indonesian Journal of Economic & Management Sciences, 2024)
This study aims to examine the level of competition and competitive strategies used by culinary businesses in Binamu District, Jeneponto Regency. This study uses qualitative methodology. This study is categorized as qualitative descriptive research based on the existing problems. The research process uses observation, interview, and documentation methodologies. The three processes needed to interpret qualitative research data are data reduction, information presentation, and drawing conclusions. The findings show that the strategies used by culinary businesses in Binamu District to increase their business turnover include choosing products that have higher market opportunities, choosing the right and strategic location, setting the right price, and improving service quality. This can be seen from the level of income that tends to increase in culinary businesses and consumers are satisfied with the culinary business offerings that are the case study in this study.